PENGGUNAAN METODE ANALISIS GLASS TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK BERKESULITAN BELAJAR MEMBACA PADA SEKOLAH DASAR - PRASETYO ARBI, RISKI (Jurnal Pendidikan Khusus, 2016)
Abstract: Based on the observation result which had been done in SDN Sidowareg I Plemahan Kediri there were several children with learning reading difficulty who had obstacle in beginning reading involving reading alphabets, and simple words. Therefore, to enhance the beginning reading ability of children with learning difficulty it was given the application of glass analysis method with picturing card and alphabet card media. This research had purpose to prove whether there was influence of using glass analysis method toward beginning reading ability of children with learning reading difficulty in SDN Sidowareg I Plemahan Kediri or not. The approach used in this research was quantitative approach. The kind of this research was pre experiment. The design used was: the one group pretest and posttest. For data analysis this research used the analysis technique of statistic non parametric. The research result after giving pretest was that the average value of children with difficulty learning was 55,4 and they were given treatment 10 times with the allocation time, 60 minutes for each meeting. Then after giving posttest indicated that the children’s value enhancement happened with the average value 60,88. From the value above, it was then analyzed using sign test value (ZH) with Z table 5% one side test 1,96. The Z value obtained in counting was ZH = 2,20 so that it could be concluded that “there was significant influence to beginning reading ability of children with learning reading difficulty” with ZH value = 2,20 > Z table 5% 1,96 so Ho was refused and Ha was accepted.   Keywords: Glass analysis, beginning reading